BETA-ADRENOBLOCKERS AND PLATELET AGGREGATION. CARVEDILOL - A. N. Zakirova; F. S. Zarudij; B. N. Garifullin (Столичная издательская компания, 2016)
Approaches evolution to studying of beta-blockers influence on platelet aggregation is reviewed. The current view on of beta-blocker antiplatelet effects is presented on the basis of physical and chemical drug properties (water repellency, dipole moment, molecular mass). Trail results on carvedilol influence on platelet aggregation are focused.